Proceedings of the 2007 Workshop on Experimental Computer Science 2007
DOI: 10.1145/1281700.1281704
|View full text |Cite
|
Sign up to set email alerts
|

The context-switch overhead inflicted by hardware interrupts (and the enigma of do-nothing loops)

Abstract: The overhead of a context switch is typically associated with multitasking, where several applications share a processor. But even if only one runnable application is present in the system and supposedly runs alone, it is still repeatedly preempted in favor of a different thread of execution, namely, the operating system that services periodic clock interrupts. We employ two complementing methodologies to measure the overhead incurred by such events and obtain contradictory results.The first methodology system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Computing in NICs avoids potentially large context switching or wake up delays for local processors, as well as data transfer latencies between the NIC and the processor that are typically significantly longer than the few cycles to perform integer addition. Context switching requires ”s [43], while waking up processors from deep sleep may require seconds [44], [45]. So the handful additional cycles required for extended precision and BigInts are negligible compared to the network time.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Computing in NICs avoids potentially large context switching or wake up delays for local processors, as well as data transfer latencies between the NIC and the processor that are typically significantly longer than the few cycles to perform integer addition. Context switching requires ”s [43], while waking up processors from deep sleep may require seconds [44], [45]. So the handful additional cycles required for extended precision and BigInts are negligible compared to the network time.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Besides, the OS memory paging represents a source of the indirect overhead since the context switch can occur in a memory page moved to the disk when there is no free memory. Prior research has shown that indirect context switch overheads [14], mainly the cache perturbation effect, are significantly larger than direct overheads.…”
Section: The Scheduling Routinesmentioning
confidence: 99%
“…Besides, the OS memory paging represents a source of the indirect overhead since the context switch can occur in a memory page moved to the disk when there is no free memory. Prior research has shown that indirect context switch overheads [9], mainly the cache perturbation effect, are significantly larger than direct overheads. We refer to the extra cache misses that occur as a result of the cache perturbation by context switching as context switch cache misses.…”
Section: Context Switch Energy Overheadmentioning
confidence: 99%